The Concept of Welfare From Siyasah Syar’iyyah Perspective and Its Implementation on Zakat Management in Indonesia - Satria Hibatal Azizy (Islamic Economics Journal, 2019)
The discourse on welfare is one discussion in economics that has been a concern for all countries in the world. By raising the issue of welfare, a government can legitimize its power. It is considered like ‘giving bread’ to the community, so that they are silent and obey to the government. In addition to that pragmatic purposes, the welfare issues also represent a moral dimension that the government pay attention to his people. In this regard, the United Nations with his UNDP formulating public welfare measure, which is called Human Development Index. Among the indicators of welfare according to this index are per capita income, long life span and level of education achieved. But behind it all, the understanding of welfare that is often understood in western economy have flaws. The welfare that is often used as a benchmark is the welfare with elements of materialism and hedonism without even the slightest attention to the religious element. It is shown from the majority-or even all-indicators of welfare that did not include religious aspects, and only made the mundane aspects as its main benchmark. This weakness shown by the phenomenon of the comforts of life in the world. Norway, a country that according to the HDI index is the most prosperous country, has a quite high suicide rate, at 28 people per 100,000 inhabitants. When compared with Egypt which ranks only 112th in the HDI, the rate of suicide is only 0.1 for each 100,000 inhabitants. This study aims to examine the concept of the budget in the perspective of siyāsah syari’iyyah and its implementation in the management of zakat in Indonesia. This paper concludes that maṣ laḥ ah is a concept in siyāsah syar’iyyah which is most appropriate in describing welfare. In the context of siyāsah syar’iyyah, zakat management in Indonesia has been regulated by the government through the Act. No. 23 of 2011, government rules. No. 14 of 2014 and derivative regulations of both. To improve the level of welfare or maṣ laḥ ah, the government also uses the CIBEST method which is integrated in the National Zakat Index, which also measures spiritual aspects in human life.